Association Between Alzheimer's Disease and Glaucoma: A Study Based on Heidelberg Retinal Tomography and Frequency Doubling Technology Perimetry - Cesareo, Massimo; Martucci, Alessio; Ciuffoletti, Elena; Mancino, Raffaele; Cerulli, Angelica; Sorge, Roberto P.; Martorana, Alessandro; Sancesario, Giuseppe; Nucci, Carlo (Frontiers in Neuroscience, 2015)
Aim: To assess the frequency of glaucoma-like alterations in Alzheimer’s disease (AD) patients using Heidelberg Retinal Tomograph III (HRT-3) and Frequency Doubling Technology (FDT) perimetry. Methods: The study included 51 eyes of 51 AD subjects and 67 eyes of 67 age- and sex-matched controls. Subjects underwent an ophthalmological examination including measurements of intraocular pressure (IOP), Matrix FDT visual field testing, optic nerve head morphology and retinal nerve fiber layer thickness (RNFLt) assessment by slit-lamp biomicroscopy and HRT-3. Results: The frequency of alterations was significantly higher in the AD group (27.5% vs 7.5%; p= 0.003; OR=4,69). AD patients showed lower IOP (p=0.000) despite not significantly different values of central corneal thickness (CCT) between the groups (p=0,336). Of all the stereometric parameters measured by HRT-3, RNFLt was significantly lower in AD patients (p=0.013). This group also had significantly worse results in terms of Moorfields Regression Analysis (p=0.027). Matrix showed significantly worse Mean Deviation (MD) (p=0,000) and Pattern Standard Deviation (PSD) (p=0,000) values and more altered Glaucoma Hemifield Test (p= 0.006) in AD patients. Pearson’s R correlation test showed that Mini Mental State Examination is directly correlated with MD (R=0,349; p = 0,034) and inversely correlated with PSD (R= -0,357; p = 0,030). Conclusion: Patients with AD have a higher frequency of glaucoma-like alterations, as detected by the use of HRT-3. These alterations were not associated with elevated IOP or abnormal CCT values.